(untitled) (Semiárida, 2020)
The aim of the present study was to evaluate the possibility of increasing the reproductive performance of the sow by reducing the normal period, without effect upon the potential production of the litter, Primiparaus sows with their litter were maintained under confinement and divided into 3 treatments with replications ach within a randomized blocks design Statistical analysis were performed through analysis of variance and test of Tukey. Treatment one (T1) consisted of a control with suckling period of 56 day. T2: 42 days and T3: 35 days. AU the 50WS received a feeding level of 1 of Iiveweight plus 300 g, on dry matter basis per suckling pig, once a day during the morning; the pigs were fed with a commercial prestarter feedsluff "ad libitum" from the 141h day lite. The parameters measured in this study were: liveweight al the end of lactation and date of first estrus alter weaning in the sows. Mean Iiveweight gain in pigs was different (P>0.05), (T1: 13.44 T2: 13.38, T3: 13.74 Kg), differences in pre-starter intake were highly significant (P<0.01) between treatments (T1: 14.45 kg, T2: 21.48 Kg, T3: 19.09 Kg), mean Iiveweights of the sows at the end of the suckling period were different (P<0.05), being the lowest one for T2,(T1: 157 Kg; T2: 139 Kg; T3: 156 Kg), probably due to the high number of suckling pigs per 50W during the 42 days of n, (T1: 6.33; T2: 9.66; T3: 6.66). One hundred percent of the sows were pregnant alter first estrus postweaning to 5 days, except for n, that required 3 more days lo appearance of first estrus. The sows receiving T1 had the lowest intake of energy and protein per suckling pig. It was concluded that a short lactation decreases pregnancy interval, although the weaning first estros period can be affected in primiparaus sows with large number of pigs/litter. The 3 weeks old pigs has already reached a complete digestive development, therefore, it is possible and easy to use early weaning as management tool.